On the issue of constraints in the construction of underground parts of civil buildings - Shumakov, I.; Saliia, М.; Mikautadze, R.; Fursov, Y. (Ways to Improve Construction Efficiency, 2019)
One of the problems that have a great influence on the technical and economic indicators of construction is buildings in the conditions of dense urban development. The facts characterizing the values of constraint are necessary to determine the degree of influence of the conditions of dense urban development construction of underground parts of civil buildings. 35 civilian buildings were examined to determine the conditions of constraint. It is established that the coefficient of constraint characteristic for the construction of civil buildings with underground parts in large cities of Ukraine changes from 0.3 to 0.8.